Invasive hepatic mucormycosis: A case report and review of the literature. Issue 1 (January 2019) - Karigane, Daiki; Kikuchi, Taku; Sakurai, Masatoshi; Kato, Jun; Yamane, Yusuke; Hashida, Risa; Abe, Ryohei; Hatano, Mami; Hasegawa, Naoki; Wakayama, Megumi; Shibuya, Kazutoshi; Okamoto, Shinichiro; et al.
Abstract: Mucormycosis generally develops under immunocompromised conditions, including hematological malignancies and solid organ or hematopoietic stem cell transplantation. Although mucormycosis usually affects the lungs and paranasal sinuses, sporadic cases of invasive mucormycosis of the liver have been reported. We hereby report a patient with myelofibrosis who developed hepatic mucormycosis diagnosed by post-mortem examination. An extensive literature review identified 13 reported cases of hepatic mucormycosis, including ours, without lung involvement. Most of the underlying diseases or conditions were hematological malignancies and solid organ transplantation. Three cases had splenic lesions and four had gastrointestinal lesions, suggesting the possibility of translocation to the liver and/or spleen from the gastrointestinal tracts. Hepatic mucormycosis should be recognized as one of the presentations of invasive mucormycosis, especially when hepatic nodules are found in immunocompromised patients such as those with hematological malignancy or recipients of solid organ transplantation.